CDC42EP4, a perisynaptic scaffold protein in Bergmann glia, is required for glutamatergic tripartite synapse configuration. (October 2018) - Ageta-Ishihara, Natsumi; Konno, Kohtarou; Yamazaki, Maya; Abe, Manabu; Sakimura, Kenji; Watanabe, Masahiko; Kinoshita, Makoto
Abstract: Configuration of tripartite synapses, comprising the pre-, post-, and peri-synaptic components (axon terminal or bouton, dendritic spine, and astroglial terminal process), is a critical determinant of neurotransmitter kinetics and hence synaptic transmission. However, little is known about molecular basis for the regulation of tripartite synapse morphology. Previous studies showed that CDC42EP4, an effector protein of a cell morphogenesis regulator CDC42, is expressed exclusively in Bergmann glia in the cerebellar cortex, that it forms tight complex with the septin heterooligomer, and that it interacts indirectly with the glutamate transporter GLAST and MYH10/nonmuscle myosin ΙΙB. Scrutiny of Cdc42ep4 −/− mice had revealed that the CDC42EP4-septins-GLAST interaction facilitates glutamate clearance, while the role for CDC42EP4-septins-MYH10 interaction has remained unsolved. Here, we find anomalous configuration of the tripartite synapses comprising the parallel fiber boutons, dendritic spines of Purkinje cells, and Bergmann glial processes in Cdc42ep4 −/− mice. The complex anomalies include 1) recession of Bergmann glial membranes from the nearest active zones, and 2) extension of nonactive synaptic contact around active zone. In line with the recession of Bergmann glial membranes by the loss of CDC42EP4, overexpression of CDC42EP4 in heterologous cells promotes cell spreading and partitioning of MYH10 to insoluble ( i.e., active) fraction. Paradoxically, however, Cdc42ep4 −/− cerebellum contained significantly more MYH10 and N-cadherin, which is attributed to secondary neuronal response mainly in Purkinje cells. Given cooperative actions of N-cadherin and MYH10 for adhesion between neurons, we speculate that their augmentation may reflect the extension of nonactive synaptic contacts in Cdc42ep4 −/− cerebellum. Transcellular mechanism that links the absence of CDC42EP4 in Bergmann glia to the augmentation of N-cadherin and MYH10 in neurons is currently unknown, but the phenotypic similarity to GLAST-null mice indicates involvement of the glutamate intolerance. Together, the unique phenotype of Cdc42ep4 −/− mice provides a clue to novel molecular network underlying tripartite synapse configuration. Highlights: Cdc42ep4−/− mouse cerebellum contains anomalous glutamatergic tripartite synapses. The anomalies include recession of Bergmann glial processes from the active zone. The anomalies include aberrant extension of synaptic contact around active zones. N-cadherin and MYH10, but not MYH9, are upregulated in Cdc42ep4−/− cerebellum. Responsibility of MYH10 and N-cadherin for the synaptic extension awaits testing.